2019
DOI: 10.1016/j.ejvs.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Critical Limb Ischaemia Exacerbates Mitochondrial Dysfunction in ApoE–/– Mice Compared with ApoE+/+ Mice, but N-acetyl Cysteine still Confers Protection

Abstract: The study shows that critical limb ischaemia (CLI) exacerbates mitochondrial dysfunction and that antioxidant therapies such as N-acetyl cysteine (NAC) still confer protection, even if comorbidities are known to reduce the protective effects of many drugs. Clinical studies using antioxidant strategies have been mostly disappointing and antioxidant therapies are still far from being integrated into treatment algorithms for peripheral arterial disease, but these results suggest that oxidative stress needs to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…ROS production was found increased in both animal models of PAD (acute ischemia-reperfusion and CLTI) as compared to controls, using either measurements of 1) free radical species by electron paramagnetic resonance spectroscopy, 2) dihydroethidium (DHE) by epifluorescence microscopy or 3) H 2 O 2 by Amplex Red perioxide assay [24,42,43]. Interestingly, ROS production was greater in PAD animals presenting with hypercholesterolemia or diabetes [26,44]. These evidences suggest an association between PAD comorbidity factors and enhanced mitochondrial dysfunction.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…ROS production was found increased in both animal models of PAD (acute ischemia-reperfusion and CLTI) as compared to controls, using either measurements of 1) free radical species by electron paramagnetic resonance spectroscopy, 2) dihydroethidium (DHE) by epifluorescence microscopy or 3) H 2 O 2 by Amplex Red perioxide assay [24,42,43]. Interestingly, ROS production was greater in PAD animals presenting with hypercholesterolemia or diabetes [26,44]. These evidences suggest an association between PAD comorbidity factors and enhanced mitochondrial dysfunction.…”
Section: Experimental Datamentioning
confidence: 99%
“…Rodent models of PAD displayed elevated protein expression of the apoptotic factors cleaved-caspase 3, cleaved-poly (ADP-robose) polymerase (PARD) and mitochondrial and cytosolic Bcl2-associated X (Bax), and reduced protein expression of the anti-apoptotic factor Bcl-2, compared with controls [21,54,55]. Furthermore, a decrease in mitochondrial calcium retention capacity was observed in ischemic limbs compared with contralateral ones (Table 5) [25,44,47,56,57]. IR increased Bax (63.4%, p = 0.020) and Bax/Bcl-2 ratio (+84.6%, p = 0.029).…”
Section: Experimental Datamentioning
confidence: 99%
“…Lejay et al [128] Swiss mice-femoral artery ligation 40 days post-surgery N-acetylcysteine -decrease tissue damage -improved mitochondrial respiration and calcium retention -decreased ROS levels Lejay et al [165] Apolipoprotein E deficient mice-femoral artery ligation 40 days post-surgery N-acetylcysteine -improved mitochondrial respiration and calcium retention -decreased ROS production Miura et al [127] Mice-femoral artery ligation 21 days post-surgery MitoTEMPO -improved limb perfusion recovery -decreased ROS production -decreased mtDNA damage…”
Section: Species and Pad Model Treatment Main Resultsmentioning
confidence: 99%
“…Recent preclinical evidence has demonstrated that treatment with antioxidant therapies show promise in both chronic ischemia and acute ischemia-reperfusion models ( Table 1). For example, Lejay et al reported that N-acetylcysteine, a global antioxidant and precursor to glutathione, improved mitochondrial respiratory function and reduced oxidative stress in mice subjected to chronic severe ischemia in both normal Swiss mice [128] and apolipoprotein E-deficient mice [165]. Another study employed a transgenic mouse overexpressing a mitochondrial-targeted catalase (scavenger of hydrogen peroxide), which was shown to decrease ischemia muscle injury and improve mitochondrial function in diet-induced diabetic mice [102].…”
Section: Therapeutic Targeting Of Mitochondria: the Future Is Bright mentioning
confidence: 99%
“…Tissues were finally harvested and dried at 150 • C for 15 min. ROS production was expressed in µmol/min/mg dry weight, as previously reported [29].…”
Section: Reactive Oxygen Species Productionmentioning
confidence: 99%